Effect of mevalonate, zoledronate and BCG on monocyte/macrophage phenotype - A. P. Lykov; S. N. Belogorodtsev; E. K. Nemkova; A. Vetlugina; T. M. Terekhova; Ya. Sh. Schwartz (Сибирский научный медицинский журнал)
Cells of innate immunity, mainly monocytes/macrophages, form a long-term nonspecific immunological memory during the initial encounter with the pathogen, the so-called trained immunity. Mevalonate pathway metabolites play an important role in the formation of trained immunity. The aim of this investigation was to study the effect of modulators of mevalonate pathway, mevalonate and zoledronate, on the formation of trained immunity in human and animal monocytes/ macrophages.Material and methods. Human monocyte-like cell lines THP-1 and U-937, peritoneal macrophages of BALB/c mice were used. Trained immunity was induced in vitro by incubation of THP-1 and U-937 monocyte-like cell lines for 24 and 72 hours with inactivated Mycobacteria of BCG vaccine strain, and in vivo by intraperitoneal administration of BCG to BALB/c mice with isolation of peritoneal macrophages on day 7 after infection (lag phase). Cell hyperreactivity was assessed by response to a second stimulus with bacterial lipopolysaccharide (LPS) and mevalonate, zoledranate in the presence or absence of LPS. Lactate, cytokine (IL-1β, TNF-α, IL-10), nitric oxide and glucose level was measured in conditioned media from cells.Results and discussion. The study showed that monocyte-like cell lines THP-1 and U-937 responded differently by cytokine production, lactate, and glucose consumption to BCG stimulus in the presence or absence of lag phase. Mevalonate and zoledronate alone or in combination with LPS also stimulated cytokine production in different ways. The presence of lag phase for human monocyte-like cells is essential for the level of cytokine production and glucose consumption. Peritoneal macrophages have been shown to enhance pro-inflammatory cytokine production in response to LPS, mevalonate, and zoledronate.Conclusions. Mevalonate and zoledronate induce trained immunity in monocytes/macrophages.